Ultrasonographic Placental Thickness Versus Fetal Outcome: A Prospective Study in Southern India - Gauri Raghunath Shinde; Nitin Kshirsagar; Manish Laddad; Vaishnavi Shivade (Babol University of Medical Sciences, 2021)
Background: Variations in placental thickness are associated with increased perinatal morbidity and mortality. However, only very few studies have been established on the correlation between placental thickness with birth outcomes. This study correlated placental thickness in 2nd and 3rd trimesters with neonatal outcome, maternal weight gain, and body mass index (BMI). Methods: A total of 116 patients aged between 20 to 50 years with singleton pregnancy and regular menstrual history (and sure about their last menstrual period) were included. Placental thickness was measured at 24 and 36 weeks by ultrasound and was divided into three groups: Group A (normal placenta), Group B (thin placenta), and Group C (thick placenta); and correlated with neonatal outcome, maternal weight gain, and BMI. Results: Out of the 116 pregnant women, 55 (47.4%) were primigravida and 61 (52.6%) were multigravida. Six patients (3.6%) delivered pre-term before 36 weeks. In the 2nd and 3rd trimesters, most cases had normal placental thickness (Group A; 93.1% and 92.7%), followed by thin placenta (Group B; 5.2% and 7.3%) and thick placenta (Group C; 1.7% and 0), respectively. Two patients with thin placenta had neonatal death. A significant positive correlation was found between birth weight and placental thickness (at 24 weeks; 0.516r, P<0.00001 and at 36 weeks; 0.669r, P<0.00001) and maternal weight gain and birth weight (0.563r, P<0.00001). Conclusion: Placental thickness on ultrasonography demonstrated well the correlation between birth weight in 2nd and 3rd trimesters and increased incidence of antenatal and postpartum complications resulting from thin placenta.